Use of Turmeric Against Escherichia coli and Staphylococcus aureus Isolated from Urinary Tract Infections: A Laboratory-Based Study - Pal, Anjila; Mahawal, Bhim S; Bom, Rabin (Journal of Institute of Medicine Nepal, 2021)
Introduction: Urinary tract infection (UTI) is an important global health problem affecting millions of peoples annually; more common among females. Among the various bacterial etiologies for UTIs, Escherichia coli is the commonest one. Turmeric has been used since ancient times as a home remedy for various medical conditions. The aim of our study is to determine the prevalence of E. coli and Staphylococcus aureus associated UTIs, their antibiogram and antibacterial effects of aqueous extracts and discs of turmeric against these isolates.Methods: All the urine samples were cultured and the isolates were identified as E. coli and S. aureus based on standard microbiological tests. Different turmeric extracts were prepared using ethanol, methanol and distilled water as solvents. Turmeric discs were also prepared by soaking the sterile filter paper discs in the different turmeric extracts. The isolated E. coli and S. aureus were tested for antibacterial activity against turmeric extracts and discs by using agar well diffusion and disc diffusion assays.Results: Out of 240 urine samples, 90 showed growth with 26.67% (24) and 5.55% (5) isolates of E. coli and S. aureus respectively. Most of the isolates were isolated from females of the age group 41-60 years. No zone of inhibition was observed for any of the bacterial isolates as well as the standard ATCC strains of E. coli and S. aureus against all the turmeric extracts. Nitrofurantoin and Gentamicin were most effective antibiotics against E. coli and S. aureus respectively.Conclusion: This study concluded that no antibacterial activity was seen for bacteria isolated from suspected cases of UTIs namely; E. coli and S. aureus against different turmeric extracts and discs.